2007
DOI: 10.1562/0031-8655(2001)0740350cpcscv2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish Procambarus clarkii shows Circadian Variations in Different Parameters of the GSH Cycle¶

Abstract: The present study investigated the rhythmic changes in glutathione status in midgut gland and hemolymph as well as in glutathione reductase (GR) activity in the crayfish Procambarus clarkii. In order to determine the circadian nature of these rhythms different groups of crayfish were submitted to constant‐darkness conditions for 24 or 72 h after they had spent 15 days under light–dark 12:12 cycles. The animals of the different batches were killed at 6 h intervals during a 24 h cycle. Reduced glutathione (GSH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Results of the current study demonstrate the presence of all GSH‐system components in crayfish retina and OL‐B. These structures show lower GSH and GSSG concentration values than those reported for hemolymph and midgut in the same species (10) as follows: LD retina GSH = 42.6 ± 3.7 μ m and GSSG = 8.6 ± 1.0 μ m ; DD retina GSH = 14.96 ± 1 μ m and GSSG = 6.12 ± 0.8 μ m ; LD OL‐B GSH = 26.4 ± 2.0 μ m and GSSG = 2.35 ± 0.2 μ m ; and DD OL‐B GSH = 12.5 ± 0.8 μ m and GSSG = 7.3 ± 1.2 μ m . Glutathione reductase and GPx also demonstrated lower activity than that reported in the same work for hepatic tissue as follows: LD retina GR = 11.7 ± 2.5 μ m NADPH ox g −1 prot min −1 ; GPX = 2.4 ± 0.4 μ m NADPH ox g −1 prot min −1 ; DD retina GR = 17.1 ± 4.2 μ m NADPH ox g −1 prot min −1 ; GPx = 10.2 ± 1 μ m NADPH ox g −1 prot min −1 ; LD OL‐B GR = 37.4 ± 4.9 μ m NADPH ox g −1 prot min −1 ; GPx = 8.3 ± 1.9 μ m NADPH ox g −1 prot min −1 ; DD OL‐B, GR = 6.7 ± 1.3 μ m NADPH ox g −1 prot min −1 ; and GPx =15.33 ± 3.8 μ m NADPH ox g −1 prot min −1 .…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…Results of the current study demonstrate the presence of all GSH‐system components in crayfish retina and OL‐B. These structures show lower GSH and GSSG concentration values than those reported for hemolymph and midgut in the same species (10) as follows: LD retina GSH = 42.6 ± 3.7 μ m and GSSG = 8.6 ± 1.0 μ m ; DD retina GSH = 14.96 ± 1 μ m and GSSG = 6.12 ± 0.8 μ m ; LD OL‐B GSH = 26.4 ± 2.0 μ m and GSSG = 2.35 ± 0.2 μ m ; and DD OL‐B GSH = 12.5 ± 0.8 μ m and GSSG = 7.3 ± 1.2 μ m . Glutathione reductase and GPx also demonstrated lower activity than that reported in the same work for hepatic tissue as follows: LD retina GR = 11.7 ± 2.5 μ m NADPH ox g −1 prot min −1 ; GPX = 2.4 ± 0.4 μ m NADPH ox g −1 prot min −1 ; DD retina GR = 17.1 ± 4.2 μ m NADPH ox g −1 prot min −1 ; GPx = 10.2 ± 1 μ m NADPH ox g −1 prot min −1 ; LD OL‐B GR = 37.4 ± 4.9 μ m NADPH ox g −1 prot min −1 ; GPx = 8.3 ± 1.9 μ m NADPH ox g −1 prot min −1 ; DD OL‐B, GR = 6.7 ± 1.3 μ m NADPH ox g −1 prot min −1 ; and GPx =15.33 ± 3.8 μ m NADPH ox g −1 prot min −1 .…”
Section: Resultsmentioning
confidence: 43%
“…The cyclic luminous condition appears to stimulate the entire GSH system in retina as a response to antagonize the oxidative effect of light on this organ. Light irradiation producing photo‐oxidation is a factor that determines ROS in different animals (1), as has been previously demonstrated in crayfish (10). In this work, both retina and brain showed higher GSH/GSSG ratio mean values in LD than in DD.…”
Section: Discussionmentioning
confidence: 69%
“…However, in the two species P. clarkii and Procambarus digueti, the antioxidant systems are known to be very robust in their diel changes (270) and entrain to light phases (271). Especially the glutathione-system in the eyestalk and the brain of P. clarkii exhibits clear-cut circadian rhythmicity (272,273).…”
Section: Melatoninmentioning
confidence: 99%
“…Circadian rhythms have been reported in a variety of physiological functions of crayfish ranging from behavioral [37-39,41,43] to cellular [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and molecular levels [12][13][14][15][16][17][18][19]. Many of these are thought to be under the control of endogenous circadian oscillators.…”
Section: Discussionmentioning
confidence: 99%
“…Crustaceans have been known to show circadian rhythms in hormonal secretion [12][13][14][15], neurosecretion [16], biogenic amine contents and actions in the central nervous system [17][18][19], mechanoreceptor sensitivity [20], photoreceptor sensitivity [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and locomotor activity [37][38][39][40][41][42][43]. A previous study in the crayfish Procambarus clarkii showed that the circadian rhythm in leg movement disappeared when the circumesophageal commissures were surgically lesioned bilaterally, thus experimentally demonstrating the importance of descending signals from the brain to posterior ganglia [38].…”
Section: Introductionmentioning
confidence: 99%